Flavonoid intake and incident hypertension in women. Issue 4 (2nd March 2016) - Lajous, Martin; Rossignol, Emilie; Fagherazzi, Guy; Perquier, Florence; Scalbert, Augustin; Clavel-Chapelon, Françoise; Boutron-Ruault, Marie-Christine
ABSTRACT: Background: Intake of flavonoid-containing food has been shown to have a beneficial effect on blood pressure in short-term randomized trials. There are limited data on total flavonoid and flavonoid-subclass consumption over a long period of time and the corresponding incidence of hypertension. Objective: We aimed to evaluate the relation between flavonoid subclasses and total flavonoid intakes and incidence of hypertension. Design: In a prospective cohort of 40, 574 disease-free French women who responded to a validated dietary questionnaire, we observed 9350 incident cases of hypertension between 1993 and 2008. Cases were identified through self-reports of diagnosed or treated hypertension. Multivariate Cox regression models were adjusted for age, family history of hypertension, body mass index, physical activity, smoking, diabetes, hypercholesterolemia, hormone therapy, and alcohol, caffeine, magnesium, potassium, omega-3 (n–3), and processed meat intakes. Results: Women in the highest quintile of flavonol intake had a 10% lower rate of hypertension than women in the lowest quintile (HR: 0.90; 95% CI: 0.84, 0.97; P -trend = 0.031). Similarly, there was a 9% lower rate for women in the highest category of intake than for women in the lowest category of intake for both anthocyanins and proanthocyanidin polymers [HRs: 0.91 (95% CI: 0.84, 0.97; P -trend = 0.0075) and 0.91 (95% CI: 0.85, 0.97; P -trend = 0.0051), respectively]. An inverse association for total flavonoid intake was observed with a similar magnitude. Conclusion: In this large prospective cohort of French middle-aged women, participants with greater flavonol, anthocyanin, and polymeric flavonoid intakes and greater total flavonoid intake were less likely to develop hypertension.